The Northern Finland Birth Cohort Eye Study: Design and baseline characteristics - Saarela, Ville (BioMed Central, 2013)
BACKGROUND: To describe the rationale and design of the Northern Finland Birth Cohort (NFBC) Eye Study. METHODS: The NFBC Eye Study is a randomised prospective cohort study. The original NFBC study population consists of 12058 subjects born in the region of Lapland and the Province of Oulu. A postal questionnaire covering extensively the medical and socioeconomical background was sent to the 10300 subjects of the NFBC alive and residing in Finland. For the NFBC eye study the subjects were randomised to the screening group (50%) and the control group (50%). The screening protocol includes the following tests: automated and manifest refraction, best corrected visual acuity, central corneal thickness, intraocular pressure, Humphrey 24–2 perimetry, stereoscopic optic nerve head (ONH) and retinal nerve fibre layer (RNFL) photography and imaging with Scanning Laser Ophthalmoscopy (HRT), Scanning Laser Polarimetry (GDx) and Optical Coherence Tomography (OCT). Two ophthalmologists evaluate the ONH and RNFL photographs and the visual fields independently. All suspected glaucoma cases are re-evaluated by two independent glaucoma experts. HRT, GDx and OCT findings are assessed separately. In the future, both groups (100%) will be examined. The effectiveness and the cost-effectiveness of glaucoma screening will be calculated. The response rate of the questionnaire was 67% (n = 6855) and 871 randomised subjects had undergone the eye screening protocol by the end of April 2013. DISCUSSION: The trial is designed to address the following questions: what is the best combination of diagnostic tests for detecting glaucoma in an unscreened population, what are the benefits and disadvantages of the screening to the individual and the society and is glaucoma screening both effective and cost-effective. The prevalence, incidence and risk factors of glaucoma and other eye diseases will be evaluated, as well as their impact on quality of life.